2016
DOI: 10.3928/01484834-20161114-10
|View full text |Cite
|
Sign up to set email alerts
|

Curricular Path to Value: Integrating an Academic Electronic Health Record

Abstract: Faculty should continue to share their innovative teaching strategies for AEHR integration. Further research should include measurable outcomes of integrating an AEHR throughout a curriculum. [J Nurs Educ. 2016;55(12):716-719.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…[5] Several studies show that a majority of faculty reported that they are self-taught regarding nursing documentation using the EHR system, and their barriers were lack of resources that lead to the slow adoption of AEHRs. [7,9,18] In addition, this study found that nurse educators still faced several challenges; a small group of nursing faculty involved, a lack of training, and a lack of a specific plan in curriculum development related to AEHRs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[5] Several studies show that a majority of faculty reported that they are self-taught regarding nursing documentation using the EHR system, and their barriers were lack of resources that lead to the slow adoption of AEHRs. [7,9,18] In addition, this study found that nurse educators still faced several challenges; a small group of nursing faculty involved, a lack of training, and a lack of a specific plan in curriculum development related to AEHRs.…”
Section: Discussionmentioning
confidence: 99%
“…The current literature shows that students are confident with their electronic nursing documentation after students explore AEHRs, [5,18] although several challenges/barriers were addressed in the current literature such as a lack of training, inadequate technical support, and cost. [5,7,9,19] One of the barriers, some faculty felt that learning electronic documentation was not a priority. [5] Several studies show that a majority of faculty reported that they are self-taught regarding nursing documentation using the EHR system, and their barriers were lack of resources that lead to the slow adoption of AEHRs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations